Relation between Different Types of Treatment and Glycemic Control in Diabetic Pregnant Women - Hakma M. Ageel; Samia Hassan (Iraqi Journal of Industrial Research)
Gestational diabetes mellitus (GDM) is a common medical condition associated with pregnancy. GDM is defined as hyperglycemia that is diagnosed during pregnancy and is not clearly overt diabetes that existed prior to pregnancy. The sample of the study was sixty diabetic pregnant women who came for follow up at obstetrics and gynecology department in TMC in Tripoli medical center during the year 2016. The patients divided according to the type of treatments they received into three groups; A: Patients who took Oral hypoglycemic agents (OHA), B: Patients who took insulin, C: Patents who took both drugs (OHA and insulin), Glycemic control was assessed using HBA1c level, FBS and RBS. This study shows that about 70% of the patients who took OHA had type 1 diabetes and 30% had type 2 diabetes. About 77.8% of patients who took insulin had type 2 diabetes and 22.2% had type 1 diabetes. And 73.2% of the patients who were treated with the combination of drugs had type 2 diabetes and 26.8% had type 1 diabetes. The current study demonstrates that 80% of patients who took OHA had good control, 33.3% of patients who took insulin had good control and 53.7% of patients who took both drugs had good control. Regarding the fasting blood sugar of the patients, the result illustrates the following; High level was reported in 20% of OHA group, 33.3% of insulin group and 31.7% of both drugs group. On the birth weight, the macrosomia (>4kg) was more in insulin group (33.3%) than other groups (10% of OHA and 31.7% of both drugs group). GDM is a condition that should be treated and prevented, as uncontrolled GDM can affect   the mother and the fetal growth.